2020
DOI: 10.2196/23830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Inhaled Ciclesonide in Treating Patients With Asymptomatic or Mild COVID-19 in the RACCO Trial: Protocol for a Multicenter, Open-label, Randomized Controlled Trial

Abstract: Background Currently, there are no specific effective treatments for SARS-CoV-2 infection; however, various COVID-19 treatment options are under investigation. It is vital to continue investigating the landscape of SARS-CoV-2–induced pneumonia and therapeutic interventions. Objective This paper presents the protocol for a randomized controlled trial that aims to compare the pneumonia exacerbation rate between ciclesonide (ALVESCO; Teijin Pharma Limited)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Regarding ICS, the Japanese Society of Infectious Diseases is leading the observational study of the administration of ciclesonide that has been found to have an antiviral effect on SARS-CoV-2. At the same time, a multicenter, open-label, randomized trial, led by the National Center for Global Health and Medicine, is underway to investigate its efficacy and safety in treating asymptomatic and mildly ill COVID-19 in patients (36).…”
Section: Table 1 Numbers and Percentages Of Asthma And Copd Comorbidmentioning
confidence: 99%
“…Regarding ICS, the Japanese Society of Infectious Diseases is leading the observational study of the administration of ciclesonide that has been found to have an antiviral effect on SARS-CoV-2. At the same time, a multicenter, open-label, randomized trial, led by the National Center for Global Health and Medicine, is underway to investigate its efficacy and safety in treating asymptomatic and mildly ill COVID-19 in patients (36).…”
Section: Table 1 Numbers and Percentages Of Asthma And Copd Comorbidmentioning
confidence: 99%
“…It was demonstrated that ciclesonide exhibited positive outcomes towards COVID-19 (Deokar et al 2021 ). Previously ciclesonide was shown to inhibit the MERS virus and inhibited the lung inflammatory process (Terada-Hirashima et al 2020 ). Previous reports suggested that the virus penetrated alveolar cells, provoking lung injury and concurrently contaminated macrophages.…”
Section: Mechanism Of Action In Covid-19mentioning
confidence: 99%
“…It has been shown that ciclesonide, an inhaled steroid drug, is associated with suppressed asthmatic attacks by reducing airway hyper-activity along with lung resistance following exposure to antigens (Terada-Hirashima et al 2020 ). Moreover, it was reported that ciclesonide suppressed the release of inflammatory mediators, slowed down the penetration of immune cells into the lung (Terada-Hirashima et al 2020 ). After inhalation, ciclesonide bound to its receptor thereafter exerted effective activities towards inflammation.…”
Section: Mechanism Of Action In Covid-19mentioning
confidence: 99%
“…7 Ciclesonide is an inhaled corticosteroid that was previously shown to reduce local inflammation in the lungs and inhibit antiviral activity against SARS-CoV-2 in in vitro studies and clinical trials are being conducted to demonstrate the efficacy in mild COVID-19. 8 , 9 A recently phase 2 trial has shown that ciclesonide inhalation shortened SARS-CoV-2 viral shedding duration, and can potentially inhibit disease progression. 10 Camostat mesylate is a well-known oral serine protease inhibitor of the human transmembrane surface protease TMPRSS2, and it is a potential antiviral drug against COVID-19.…”
Section: Introductionmentioning
confidence: 99%